2006
DOI: 10.1134/s1087659606030138
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of CuCr2Se4 ferromagnetic spinel nanocrystals

Abstract: Polycrystalline and nanocrystalline samples of the CuCr 2 Se 4 ferromagnetic spinel are synthesized. The mean size of nanocrystals is 50 nm. The Curie temperature of spinel nanocrystals (465 K) is higher than that of spinel polycrystals (435 K). Laser irradiation at a wavelength of 1.5 µ m (in an external magnetic field) increases the magnetization of the noncrystalline powder. Most likely, this can be explained by the change in the orientation of magnetic moments of single-domain nanoparticles. The observed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In relation to NCs, slightly different magnetic activities were reported, depending on the NC synthetic method which was employed. For example, magnetic measuremernts of CuCr 2 Se 4 NCs (synthesized from microwave radiation) showed a saturation magnetization of 15 emu g −1 and a coercive force of 80 Oe at room temperature. In another report, agglomerated CuCr 2 Se 4 NCs (particle sizes between 25 and 200 nm) were formed in a solvothemal synthesis approach, in which a Curie temperature of 450 K presented saturation magnetization of 2.3 μ B per Cr atom at 5 K . Similar results were also reported by Rao et al A colloidal approach reported by Wang et al allowed for much better size control of the resultant CuCr 2 Se 4 NCs, in which hysteresis loops for NCs, with an average size of 15 and 25 nm, were measured at 300 and 10 K, respectively .…”
Section: Functional Propertiessupporting
confidence: 65%
“…In relation to NCs, slightly different magnetic activities were reported, depending on the NC synthetic method which was employed. For example, magnetic measuremernts of CuCr 2 Se 4 NCs (synthesized from microwave radiation) showed a saturation magnetization of 15 emu g −1 and a coercive force of 80 Oe at room temperature. In another report, agglomerated CuCr 2 Se 4 NCs (particle sizes between 25 and 200 nm) were formed in a solvothemal synthesis approach, in which a Curie temperature of 450 K presented saturation magnetization of 2.3 μ B per Cr atom at 5 K . Similar results were also reported by Rao et al A colloidal approach reported by Wang et al allowed for much better size control of the resultant CuCr 2 Se 4 NCs, in which hysteresis loops for NCs, with an average size of 15 and 25 nm, were measured at 300 and 10 K, respectively .…”
Section: Functional Propertiessupporting
confidence: 65%
“…Copper selenide nanoparticles are mostly found as CuSe, Cu 2 Se and Cu 3 Se 2 with their bulk materials possessing band gap energy between 1 and 2.3 eV [4,5]. Various results have been reported for the synthesis of Cu x MSe 4 (M = Sb [6,7], P [8], Sn [9], Cr [10,11], As [12]) nanoparticles. These methods resulted in various shaped and sized particles.…”
Section: Introductionmentioning
confidence: 99%
“…Based on wet chemical colloidal synthesis technology, they have successfully obtained a series of phase-pure Cr-based chalcospinel nanocrystals, which greatly contributed to the development of this material system. Meanwhile, some other synthesis techniques, including the microwave-assisted polyol method, mechanical alloying, thermal decomposition, solvothermal reactions, and sonochemical synthesis, have also been successfully applied to the preparation of Cr-based chalcospinels. In addition, ACr 2 X 4 thin films have also been fabricated by chemical deposition, physical deposition, and electrodeposition .…”
Section: Introductionmentioning
confidence: 99%